THE IMPACT OF FINTECH ON FINANCIAL INCLUSION: EXPANDING ACCESS TO FINANCIAL SERVICES - Jana, Debashree Souvik (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research looks at how FinTech has changed financial inclusion in India, focusing on how it has improved access to loans, insurance, savings, and sending money back to family and friends abroad. Even though there have been big steps forward, problems like limited internet access, digital literacy, regulatory hurdles, and a lack of funds are slowing its growth. The study looks at trends, problems, and possible futures by using secondary data from trustworthy sources. It says that India needs to keep coming up with new technologies, policies that help them, partnerships, and financial education programmes in order to use FinTech to close the financial inclusion gap and boost economic growth.